Lying About Hitler: History, Holocaust, and the David Irving Trial - Cesarani, David (Holocaust and genocide studies, 2002)
Lying About Hitler: History, Holocaust, and the David Irving Trial Richard J.Evans New YorkBasic Books 2001318$27.00 , 1University of Southampton and AHRB Parkes Centre for the Study of Jewish/non‐Jewish Relations